Ukraine : Ex Post Evaluation of Exceptional Access Under the 2008 Stand-By Arrangement. (IMF Staff Country Reports; Country Report, 2011)
Ukraine was one of the countries hardest hit by the global economic and financial crisis; it was also one of the first countries supported by a Stand-By Arrangement (SBA). The Ex Post Evaluation of Exceptional Access Under the 2008 SBA reveals that the achievement of program objectives was mixed, with core short-term objectives largely met, but little progress made toward meeting medium-term objectives. The banking system stabilized, the current account adjusted quickly, social arrears and sovereign default were avoided, and a gradual economic recovery started from mid-2009.